Cu–Pd bimetallic nanoalloy anchored on a N-rich porous organic polymer for high-performance hydrodeoxygenation of biomass-derived vanillin. Issue 8 (4th April 2018) - Shit, Subhash Chandra; Singuru, Ramana; Pollastri, Simone; Joseph, Boby; Rao, Bolla Srinivasa; Lingaiah, Nakka; Mondal, John
Abstract : A N-rich porous organic polymer-anchored bimetallic Cu–Pd nanoalloy exhibited superior catalytic activity with improved stability for biomass-derived selective hydrodeoxygenation of vanillin. Abstract : The structural composition, particle size on the nanoscale, phase state, and surface property have a significant impact on the performance of nanoalloy catalysts. Here we report a bimetallic Cu3 Pd nanoalloy anchored on a N-rich porous organic polymer (BBA-1), Cu3 Pd@BBA-1, which shows enhanced catalytic activity for the hydrodeoxygenation of vanillin, a typical compound of lignin-derived bio-oil. The prepared Cu3 Pd @BBA-1 bimetallic nanocatalyst exhibits highly efficient catalytic performance in promoting biomass refining compared with its monometallic counterparts, providing 99.3% conversion of vanillin with an exclusive selectivity of 93.6% for the hydrogenolysis product 2-methoxy-4-methylphenol. This catalyst is also found to have superior stability (reproducible conversion values upon several cycles), which represents a significant step forward in promoting biomass refining. The Cu3 Pd@BBA-1 and related Cu and Pd based catalysts with varying metallic molar ratios were synthesized by a polyol method using NaBH4 as a strong reducing agent. The specific textural and chemical characteristics of the as-synthesized nanohybrid materials were comprehensively investigated by performing X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, synchrotron powder diffraction, X-ray absorption fine structure spectroscopy, 13 C cross polarization magic angle spinning nuclear magnetic resonance, nitrogen physisorption, high resolution transmission electron microscopy, and high angle annular dark field scanning transmission electron microscopy with the corresponding elemental mapping. The catalytic performance of Cu3 Pd on other commercial supports such as Al2 O3, TiO2 and N-doped carbon is found to be inferior to that on BBA-1, revealing the important role of the nitrogen-rich porous organic polymer matrix. The performance of a 3 : 1 mixture of the monometallic nanoalloys was substantially lower than that of Cu3 Pd@BBA-1. These results and the inputs from the experimental probes used for the characterization indicate that in Cu3 Pd@BBA-1, alloying leads to improved surface conditions on the nanoscale and brings about a synergetic electronic effect, thus enabling an enhanced catalytic activity and good recyclability.